Pseudomonas aeruginosa gene PA4880 encodes a Dps-like protein with a Dps fold, bacterioferritin-type ferroxidase centers, and endonuclease activity - Rajapaksha, Nimesha; Yao, Huili; Cook, Aisha; Seibold, Steve; Liu, Lijun; Battaile, Kevin P.; Fontenot, Leo; Donnarumma, Fabrizio; Lovell, Scott; Rivera, Mario (Frontiers in Molecular Biosciences, 2024)
We report the biochemical, structural, and functional characterization of the protein coded by gene PA4880 in the Pseudomonas aeruginosa PAO1 genome. The PA4880 gene had been annotated as coding a probable bacterioferritin. Our structural work shows that the product of gene PA4880 is a protein that adopts the Dps subunit fold, which oligomerizes into a 12-mer quaternary structure. Unlike Dps, however, the ferroxidase di-iron centers and iron coordinating ligands are buried within each subunit, in a manner identical to that observed in the ferroxidase center of P. aeruginosa bacterioferritin. Since these structural characteristics correspond to Dps-like proteins, we term the protein as Pseudomonas aeruginosa Dps-like, or Pa DpsL. The ferroxidase centers in Pa DpsL catalyze the oxidation of Fe 2+ utilizing O2 or H2O2 as oxidant, and the resultant Fe 3+ is compartmentalized in the interior cavity. Interestingly, incubating Pa DpsL with plasmid DNA results in efficient nicking of the DNA and at higher concentrations of Pa DpsL the DNA is linearized and eventually degraded. The nickase and endonuclease activities suggest that Pa DpsL, in addition to participating in the defense of P. aeruginosa cells against iron-induced toxicity, may also participate in the innate immune mechanisms consisting of restriction endonucleases and cognate methyl transferases.